Incidencia del movimiento de mujeres de El Oro en la lucha por la garantía de derechos y equidad de género de la parroquia Puerto Bolívar del cantón Machala del año 2013. - Campuzano Portilla, Shirley Johana (2014)
This research work entitled "IMPACT OF WOMEN'S MOVEMENT OF GOLD IN THE STRUGGLE FOR THE GUARANTEE OF RIGHTS AND GENDER EQUITY PARISH OF PORT BOLIVAR MACHALA CANTON OF YEAR 2013-2014" as a way to access knowledge cultural social class. In this paper gender equity is developed to interact with the text and context for developing emotional integrity that contributes to their social growth, it promotes renewal, adapting reflective, creative thinking and working on activities and values ​​to be established emotional balance to achieve useful and productive to society requires us both the realization of scheduled events and palicación knowledge of Ecuadorian culture centered on the reality of life and meets diadria objective which society requires people has drawn the implementation of this project, because not only will bring about learning but also serves as a base to motivate and appreciate the continuing pportunities shower, for the guarantee of their rights and so will benefit from this project will receive aspirations for improve and strengthen the performance of gender equity, which work to the benefit of society orense.